Theoretical and Conceptual Framework for an Assessment on how inclusive Environment Hinders Pupils with Dyslexia Academically in two Secondary Schools in Kabwe - Nyirenda Tisiye Esther; Penda Annie , (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
This manuscript is an extract of a theoretical framework and conceptual framework from a Master’s an on-going study of an assessment on how inclusive environment hinders pupils with dyslexia academically in two secondary schools in Kabwe in Zambia. Among the factors that can affect these learners are such as environment, cognitive and behavioral. It is argued that if these factors are identified and addressed learners with dyslexia can benefit a lot academically under inclusive education system.